Analysis of the Implementation of a Smart Fire System On/Off Prototype Using a Solenoid Valve and Notification Based on Arduino Uno - Suhardi Siagian; Solly Aryza; Hamdani, Hamdani (INFOKUM, 2025)
Fire detection and prevention systems are important aspects in maintaining environmen-tal security, both at home and in public facilities. This study aims to develop and analyze the implementation of an Arduino Uno-based Smart Fire System On/Off prototype equipped with a solenoid valve for automatic fire extinguishing and application-based notification. This system consists of a temperature and smoke sensor as the main detec-tor, an Arduino Uno as a controller, a solenoid valve to regulate water flow, and a com-munication module to send notifications to users. Tests were conducted to evaluate the system's response speed, detection accuracy, and the effectiveness of the automatic fire extinguishing mechanism. The results show that this system is able to detect potential fires with 95% accuracy and provide notifications to users in less than 5 seconds after detection. In addition, the solenoid valve is successfully activated automatically to extin-guish the fire with a success rate of up to 90%. This prototype shows potential for im-plementation as an efficient fire safety solution, especially at the household and small business scale.